A Study on Consumer Buying Behaviour and Awareness of Infant Food Formula in Anand and Vidyanagar - , Henil S. Patel, K.C. Kamani, M.C. Prajapati, A.K. Makwana, M.D. Gurjar (Archives of Current Research International, 2025)
The infant food formula industry is witnessing notable growth, particularly in developing countries like India, due to evolving family structures, increased maternal employment, and heightened awareness of infant nutrition. This study investigates consumer awareness, usage patterns, and perception of infant food formula among residents of Anand and Vallabh Vidyanagar. Primary data were collected from 98 respondents through structured questionnaires distributed across medical stores, children's hospitals, and maternity homes. The results reveal that only 42% of participants were aware of infant formula products, and awareness was mainly driven by retail exposure and personal networks. Among the aware respondents, 80% had tried the product, although usage was largely occasional, suggesting its role as a supplement rather than a replacement for breastfeeding. The study highlights high consumer satisfaction regarding nutritional quality and convenience, but also identifies significant dissatisfaction with product availability. Key factors influencing purchase decisions include insufficient breast milk, medical advice, and product convenience. These insights underscore the need for improved awareness, strategic marketing, and better distribution to enhance product adoption. The findings offer valuable implications for manufacturers and healthcare stakeholders aiming to bridge the gap between consumer expectations and product offerings in the infant nutrition sector.